PENGEMBANGAN DESAIN SERTA ANALISIS PELUANG PASAR PRODUK AMPERA: ALAT PEMBERSIH PERALATAN LABORATORIUM OTOMATIS: Indonesia - Rita Arlistia; Riska Novianti; Wilda Waliam Mursyida; Syifa Maulani Insira; Aldis Muhammad Hanif (UII, 2022)
Abstract This research is motivated by the lack of effective and efficient washing of laboratory equipment. This is because manual cleaning of laboratory equipment still leaves plaque on laboratory equipment. The purpose of this research is to overcome problems related to manual washing of laboratory equipment. The stages of this research include observation, preparation of tools and materials, purchase of tools and materials, stages of production and marketing. The results of the survey, laboratory equipment that is often used in the form of measuring cups, dropper pipettes and Erlenmeyer, the range of the hand circumference cannot reach the measuring cup 90.5%, the hand cannot reach the bottom surface of the tool 88.4%, the effectiveness of washing dropper pipettes with a brush is 74 .4%, manual washing of laboratory equipment was deemed ineffective 74.4%, 100% automatic laboratory cleaning products were not found, 100% interest in laboratory equipment cleaning products were found, 90.7% of plaque was found on the equipment after washing. Based on this, we created an innovative automatic laboratory equipment cleaning tool (AMPERA) as a solution to this problem.